Strategi Integrasi Nilai-Nilai Islam dalam Kurikulum Merdeka untuk Pembentukan Karakter - Siti Rohmaniah; Marsino; Kurniawan, Wakib (TAUJIH: Jurnal Pendidikan Islam, 2025)
The character crisis among Indonesian youth poses a serious challenge in the field of education, especially in the era of globalization and digitalization that massively introduces external values. The Merdeka Curriculum emerges as an educational reform initiative emphasizing character development through flexible learning and the reinforcement of the Pancasila Student Profile. However, there remains a lack of systematic studies on practical strategies to integrate Islamic values into the implementation of the Merdeka Curriculum in a way that effectively supports holistic character formation. This study aims to analyze strategies for integrating Islamic values into the implementation of the Merdeka Curriculum to enhance the effectiveness of character development. A qualitative descriptive approach is employed using library research methods, examining recent academic literature and education policies (2019–2024). Data analysis was conducted using thematic analysis, with source triangulation to ensure validity. The findings indicate that Islamic values can be integrated through several learning strategies, such as thematic-integrative approaches, project-based learning, problem-based learning, cross-disciplinary teacher collaboration, and the use of Islamic digital technologies. These strategies enable the contextual and practical internalization of Islamic moral values while supporting the development of 21st-century competencies. The implications highlight the urgent need to enhance the capacity of Islamic education teachers (PAI) in designing holistic learning strategies aligned with the principles of the Merdeka Curriculum and Islamic values. This study provides conceptual and practical contributions to the development of Islamic education that is relevant, moderate, and transformative.